Verb Valency Frame Extraction Using Morphological and Syntactic Features of Croatian - Šojat, Krešimir; Tadić, Marko; Agić, Željko (2010)
The paper presents an approach to valency frame extraction for Croatian verbs on basis of morphological and syntactic features of wordforms from syntactically annotated sentences. We have used a gold standard sample of approximately 1200 sentences and 30.000 tokens from the Croatian Dependency Treebank and a frame instance extraction algorithm. We extracted 936 verb frame instances for 424 different verbs – consisting of lemmas, morphosyntactic tags and syntactic functions of the encountered wordforms – and manually assigned tectogrammatical functors to their elements. Distributional properties are given in terms of co-occurrences for each of these features. The obtained results will serve for further development of valency frame extraction procedures.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG